Asociación entre disminución de la sensibilidad parasitaria in vitro y respuesta terapéutica en pacientes con Leishmaniasis cutánea tratados en el centro dermatológico Federico Lleras Acosta de la ciudad de Bogotá entre 2006 y 2012 (2021)
Cutaneous leishmaniasis is a neglected tropical disease, broadly distributed in the planet and with high incidence among socially vulnerable persons. It has been underestimated by healthcare systems and society, with a great burden of disease. Despite an available effective and well established treatment since the 50’s, it has been documented an increasing rate of resistance and treatment failure. Reports in Latin America, show resistance rates between 10-20% and 25% of subjects with treatment failure using first line drugs. Nevertheless, there is no clear association between reduced in vitro susceptibility from the parasite and treatment response. This case control study with 34 subjects in a reference center in Bogotá, aimed to establish an association between reduced in vitro susceptibility and response to treatment. The results showed an OR 0.71 (IC 95% 0.085 – 9.39), which possibly means that there is no relation among the mentioned variables. These results suggest that susceptibility testing would not impact clinical decision making as treatment failure predictors, therefore limiting its systematic use